Endogenous circadian temperature rhythms relate to adolescents’ daytime physical activity - Kuula, Liisa; Lipsanen, Jari; Partonen, Timo; Kauramäki, Jaakko; Halonen, Risto; Pesonen, Anu-Katriina (Frontiers in Physiology, 2022)
Circadian rhythms relate to multiple aspects of health and wellbeing, including physical activity patterns. Adolescents’ circadian regulation is particularly vulnerable, and may lead to sedentary behavior. We investigate how individual characteristics of habitual circadian patterns associate with objectively measured physical activity (PA). We studied 312 adolescents (70% females), mean age 16.9 y. Circadian period length, temperature mesor and amplitude were measured using distally attached thermologgers (ibutton 1922L, 3-day-measurement). We additionally utilized algorithm-formed clusters of circadian rhythmicity. Sleep duration, timing, delayed sleep phase (DSP) and PA were measured using actigraphs (GeneActiv Original, 10-day-measurement). We found that continuous circadian period length was not associated with PA, but lower mesor and higher amplitude were consistently associated with higher levels of PA as indicated by mean Metabolic Equivalent (METmean) and moderate-to-vigorous PA (MVPA), even when controlling for sleep duration. Separate circadian clusters formed by an algorithm also reflected distinct patterns of PA accordingly. Late sleepers and those with DSP were less likely to engage in MVPA compared to non-DSP, and had more sedentary behavior. Adolescents who engage in higher levels or high-intensity PA have better circadian regulation, as measured by different objective methods including distal temperature measurements as well as actigraphy-measured sleep-wake behavior.